PENGARUH DIMENSI SERVICESCAPE TERHADAP KEPUASAN NASABAH DI MASA PANDEMI COVID-19 - Juita Lubrina Domina Bessie; Lucky Y.T. Boimau (Journal of Management Small and Medium Enterprises (SMEs), 2022)
This study aims to determine the Effect of the Servicescape Dimensions toward Customer of BRI Cabang Kupang's Satisfaction during the COVID-19 pandemic. The independent variable in this study is the servicescape dimension consisting of Ambient conditions s, spatial layout and functionality, and signs, symbols, and arifacts, while the dependent variable is customer satisfaction.The number of samples in this study as many as 100 respondents, who come to transact at BRI Cabang Kupang. That samples obtained using accidental sampling techniques. The data was collected using questionnaires, interviews, and literature studies. The data analysis techniques used are quantitative descriptive, multiple linear regression analysis and hypothesis testing using SPSS 26 applications.The results of the descriptive analysis show that overall the respondents give a very good perception of the three dimensions of servicescape which applied by BRI Cabang Kupang. From the results of Multiple Linear Regression Analysis obtained the mathematical equationn: Y = 8,192 + 0,494X1 + 0,241X2 + 0, 826X3. Both the t test and F test results show that simultaneously and partially the three servicescape dimensions have a significant effect on customer satisfaction. Based on the Adjusted R2 value, it shows the contribution of the Servicescape dimensions toward customer satisfaction by 66,1%. While 33,9% is influenced by other variables outside the focus of this study. The other variable is the service quality that can be taken into consideration for further researchers in addition to the existing variables. Keywords: Servicescape, Ambient Conditons, Spatial Layout And Functionality, Signs, Symbols And Artifacts, And Customer Satisfaction.